SERS Quantification of Galunisertib Delivery in Colorectal Cancer Cells by Plasmonic‐Assisted Diatomite Nanoparticles (Small 34/2021). Issue 34 (26th August 2021) - Managò, Stefano; Tramontano, Chiara; Delle Cave, Donatella; Chianese, Giovanna; Zito, Gianluigi; De Stefano, Luca; Terracciano, Monica; Lonardo, Enza; De Luca, Anna Chiara; Rea, Ilaria
Abstract : Drug Delivery Systems In article number 2101711, Enza Lonardo, Anna Chiara De Luca, Ilaria Rea, and co‐workers demonstrate the small molecule Galunisertib with anticancer activity loaded inside a hybrid multifunctional nanosystem made of porous biosilica covered by plasmonic gold nanoparticles. The pH‐triggered‐LY release inducing mesenchymal to epithelial transition in colorectal cancer cells is monitored and quantified with sub‐femtogram resolution by intracellular SERS analysis.